Organizational Culture Assessment: Analysis The Strategy of “BE STRONG” in University of Lampung - Habibullah Jimad; Luthfi Firdaus; Yuningsih Yuningsih (Jurnal Mirai Management, 2026)
This research analyzes the implementation of the “BE STRONG” strategy in strengthening organizational culture at the University of Lampung. Using a mixed-methods approach with descriptive analysis, this study combines quantitative and qualitative techniques to obtain a comprehensive understanding of organizational culture dynamics within the university environment. The research applies the Organizational Culture Assessment Instrument (OCAI) and Management Skills Assessment Instrument (MSAI) to identify organizational culture preferences and managerial competencies. Data were collected through purposive sampling involving 23 respondents representing lecturers, staff, and leaders at the Rectorate, Faculty, Bureau, Institution, and Technical Implementation Unit levels, selected based on their roles, involvement, and understanding of organizational processes and culture. The results reveal the dominance of Hierarchy and Adhocracy cultures, reflecting the need for stability through structured control alongside flexibility and adaptive innovation. The findings indicate that the implementation of the “BE STRONG” strategy has succeeded in strengthening risk-based governance and structured information systems (Hierarchy), although innovation in learning and research (Adhocracy) still requires improvement. This research recommends strengthening governance systems alongside developing competencies such as Managing Risk and Managing Innovation. These findings contribute to the development of a stable, adaptive, and innovative organizational culture, supporting the University of Lampung in achieving its vision as a World Class University (WCU).